Comparative study for modal analysis of circular plates with various cutouts and end conditions - Bhatnagar, Vedanth; Mamaduri, Pavan Kishore; B, Sreenivasulu (Vibroengineering Procedia, 2019)
The applicational use of structural members in engineering and technology may take the form of a circular plate, for such members it becomes important to predict the vibrational characteristics when operated closer to resonance phenomena. In addition to, the effect of the cutout in the circular plate has a significant effect on modal characteristics. The part of the research work entitled in this paper emphasizes on the modal analysis of a circular plate with clamped boundary condition determined by the characteristics equation and mode shapes of the plate using FEM. The effects of inclusion of cut-out on the vibrational characteristics are discussed. The subject of the analysis was a circular plate considered with certain modifications i.e. free circular plate without cutout clamped on the outer periphery, circular plate with cut-out clamped on the outer periphery, circular plate with cutout clamped on the outer and inner periphery. The methodology applied to conventional material based circular plate is extended to Glass epoxy circular plate with the same set of modifications. The values of natural frequencies for various cases are tabulated and corresponding mode shapes are illustrated.